Solar cycles and time allocation of children and adolescents - Ha Trong Nguyen; Stephen R. Zubrick; Francis Mitrou (Global Labor Organization (GLO), 2024)
This study explores the allocation of time, particularly to sleep, among children and adolescents in response to daily solar cycles. Utilizing a dataset of over 50,000 time-use diaries from two Australian cohorts spanning 16 years and employing an individual fixed effects estimator, we uncover a significant correlation between daylight duration and sleep patterns. Our findings reveal that days with longer daylight hours are associated with a decrease in total sleep duration, driven primarily by later sleep onset and earlier wake times. Additionally, longer daylight hours correspond to reduced time spent on personal care and media activities, with increased dedication to school and physical activities. Furthermore, we identify socio-demographic factors moderating these effects, such as older age and weekdays exerting a stronger influence on sleep duration, while children of mothers with lower education or unemployment exhibit a subtle impact. These insights contribute to our understanding of how environmental factors shape daily routines and offer implications for designing schedules that promote positive developmental outcomes in young individuals.
Keywords: I00; I12; J22; J24; 330; Sleep; Time Allocation; Circadian Rhythms; Solar Cycles; Children